(untitled) (The Journal of Plant Protection Sciences, 2022)
Muga, the golden-yellow silk is obtained from semi-domesticated silkworm called Antheraea assamensis Helfer. Muga culture is an age-old practice in the Brahmaputra valley of Assam. However, in recent years production of muga silkworm seed crops is adversely affected in Assam with the rise of temperature due to global warming. Kalimpong (latitude 27°06 N, longitude 88°47 E, 1247 m above msl) is one of the potential zones for production of muga seed during June-July and August September crop. Accordingly, primary food plant of muga silkworm (Antheraea assamensis Helfer) viz. Som [Persea bombycina (King ex Hook. f.) Kosterm] (Family: Lauraceae)] and Soalu [Litsaea monopetala (Roxb) Pearson] (Family: Lauraceae) has been raised in large scale on the hilly terraces of Kalimpong. The food plants are usually attacked by many pests like shoot borer, trunk borer, leaf min ers, leaf galls, mealy bugs (3).